Self-regulation model applied to menopause: a mixed-methods study. (2nd January 2020) - Pimenta, F.; Ramos, M. M.; Silva, C. C.; Costa, P. A.; Maroco, J.; Leal, I.
Abstract: Objectives: Considering that bio-psycho-sociocultural variables influence menopause, this research aimed to assess the suitability of the self-regulation model in explaining the menopausal experience, and to explore differences among participants with different characteristics (e.g. health, sexual related) regarding menopause representations. Methods: Overall, 27 Portuguese women aged 40–65 years were assessed for sociodemographics, health, and sexual activity, as well as menopausal status and symptoms. Semi-structured in-depth interviews were conducted. A directed content analysis was performed, and the qualitative data presented. Afterward, the frequencies of the categories were analyzed through quantitative methods (Mann–Whitney U tests). Results: Aging was the most frequently mentioned feature regarding menopause Identity, whereas vasomotor symptoms were the most mentioned regarding Negative Consequences and menses cessation regarding Positive Consequences. Features related to Cause (hormonal changes) and Control (need for acceptance) of menopause were also identified. No differences were found in the frequency of menopause representations between women with different characteristics (e.g. with higher vs. lower vasomotor symptom severity). Conclusion: The suitability of the self-regulation model to explain these women's menopause experience was confirmed and the representations did not vary among participants with different characteristics. This research might help professionals and researchers in developing comprehensive interventions, based on this theoretical model.